2015
DOI: 10.1080/02786826.2015.1086724
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Study on Charge Decay of Electret Filter Due to Organic Solvent Exposure

Abstract: The electret filter is a potential component to remove airborne particles due to its high collection efficiency and low pressure drop. However, its filtration performance is gradually decreased by exposure to organic solvents, which limits the application of electret filters. The effect of ethanol exposure on the filtration performance of polypropylene electret filters was investigated experimentally to clarify the charge decay phenomenon in this study. Experimental results revealed that filter performance is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
37
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(37 citation statements)
references
References 17 publications
0
37
0
Order By: Relevance
“…Although electret filters reach a high initial filtration efficiency, it is known that the efficiency can drastically degrade with time due to exposure to particles , , organic solvents , or air humidity . This is usually denoted as aging of the filters and may be related to either compensation or shielding of the fiber charges or to chemical interactions between the aerosol and the filter material .…”
Section: Introductionmentioning
confidence: 99%
“…Although electret filters reach a high initial filtration efficiency, it is known that the efficiency can drastically degrade with time due to exposure to particles , , organic solvents , or air humidity . This is usually denoted as aging of the filters and may be related to either compensation or shielding of the fiber charges or to chemical interactions between the aerosol and the filter material .…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the performance of a filter was affected by the electrostatic force condition on the filter. Previous research showed that ethanol treatment to neutralize a filter significantly decreased the particle collection efficiency (Lee et al, 2002;Choi et al, 2015). The effect of diffusion and field charging did not significantly affect particle collection efficiency for the combination of the unipolar charger and electret filters because the short distance of 25 mm does not improve the collection efficiency.…”
Section: Voltage-current Characteristicsmentioning
confidence: 88%
“…The effect of a filter was studied by utilizing a fresh film-type electret filter (FF) and a neutralized film-type electret filter (NF). The NF was prepared by soaking an electret filter in an ethanol solution and drying it at room temperature for 72 hours (Lee et al, 2002;Choi et al, 2015).…”
Section: Corona Discharging Zonementioning
confidence: 99%
“…21 Besides that, studies showed that unsaturated vapors of organic solvents do not lead to any discharge of the fibrous material. 21,26 To explain and understand the discharging mechanisms of electret fibers in detail, experimental evidence and further research are needed.…”
Section: Dischargingmentioning
confidence: 99%